Internet technology usage and female employment: Evidence from a Chinese general social survey - Gao, Jiacheng; Liu, Yue (The Economics and Finance Letters, 2023)
This study empirically analyzes the effect of internet technology usage on female employment and their wage income by constructing logit and quantile regression models to examine the moderating effect of years of education. The results show that internet technology usage significantly suppresses the likelihood of female employment and reduces their wage income before their years of education reach the target requirement but has a differential effect on the wage income of females at different levels. After females have reached their years of education target, internet technology usage significantly increases their likelihood of obtaining employment and improving their wage income. The positive effect of internet technology usage on female employment and their wage income is more obvious as the years of education increases. Therefore, this study proposes that females should be encouraged to strengthen their internet technology usage skills and improve their education level.